Cannibalism in northern giant petrels ( Macronectes halli ) at Possession Island, Southern Indian Ocean - Alexandre Vong; Karine Delord; Nicolas Croizé; Célia Lesage; Lucía Llorente Zubiri; Florent Sabatier; Christophe Barbraud (Ecology, 2025)

Dispersal syndromes in challenging environments: A cross‐species experiment - Julien Cote; Maxime Dahirel; Nicolas Schtickzelle; Florian Altermatt; Armelle Ansart; Simon Blanchet; Alexis S. Chaine; Frederik De Laender; Jonathan De Raedt; Bart Haegeman; Staffan Jacob; Oliver Kaltz; et al. (Ecology Letters, 2022)
Dispersal is a central biological process tightly integrated into life‐histories, morphology, physiology and behaviour. Such associations, or syndromes, are anticipated to impact the eco‐evolutionary dynamics of spatially structured populations, and cascade into ecosystem processes. As for dispersal on its own, these syndromes are likely neither fixed nor random, but conditional on the experienced environment. We experimentally studied how dispersal propensity varies with individuals' phenotype and local environmental harshness using 15 species ranging from protists to vertebrates. We reveal a general phenotypic dispersal syndrome across studied species, with dispersers being larger, more active and having a marked locomotion‐oriented morphology and a strengthening of the link between dispersal and some phenotypic traits with environmental harshness. Our proof‐of‐concept metacommunity model further reveals cascading effects of context‐dependent syndromes on the local and regional organisation of functional diversity. Our study opens new avenues to advance our understanding of the functioning of spatially structured populations, communities and ecosystems.

Dispersers are more likely to follow mucus trails in the land snail Cornu aspersum - Alexandre Vong; Armelle Ansart; Maxime Dahirel (The Science of Nature, 2019)